Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0954411911400156
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and model validation of selective spinal cord and brain hypothermia induced by a simple torso-cooling pad

Abstract: In vivo experiments have been performed to test the effectiveness of a torso-cooling pad to reduce the temperature in the spinal cord and brain in rats. Coolant was circulated through the cooling pad to provide either mild or moderate cooling. Temperatures in the brain tissue, on the head surface, and on the spine and back surfaces were measured. During mild cooling, the temperature on the back surface was 22.82 +/- 2.43 degrees C compared to 29.34 +/- 1.94 degrees C on the spine surface. The temperature on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Previous studies have identified hypothermia systems (neckbands or torso-cooling pads) as efficient devices for lowering temperature of the brain and/or spinal cord locally [63,64]. We have previously shown that a local MTH approach is feasible in preclinical models of cochlear implant insertion trauma without wide systemic effects and confirmed the spatial localization in human cadaver bones locally [44,45].…”
Section: Pro-inflammatorysupporting
confidence: 64%
“…Previous studies have identified hypothermia systems (neckbands or torso-cooling pads) as efficient devices for lowering temperature of the brain and/or spinal cord locally [63,64]. We have previously shown that a local MTH approach is feasible in preclinical models of cochlear implant insertion trauma without wide systemic effects and confirmed the spatial localization in human cadaver bones locally [44,45].…”
Section: Pro-inflammatorysupporting
confidence: 64%
“…Similar approach was employed to simulate hypothermia treatments to lower the brain temperature and identified a neckband, covering the carotid triangles of the neck, as a successful technique (Keller et al 2009). Theoretical and in-vivo experiments showed the effectiveness of a torso-cooling pad to reduce the temperature in the spinal cord and brain in rats (Smith 2011). Following these studies, we utilized Pennes bio-heat equation and finite element analysis to simulate the temperature distribution in the cochlea during therapeutic hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to avoid effects on coagulation, it would be worth investigating whether selective spinal cord cooling can be aimed and achieved for spinal cord protection during TAAA surgeries. Both invasive devices 5 (epidural catheters infusing cold epidural solutions) as well as noninvasive devices 6 (underbody torso-cooling pads) have been experimented for selective spinal cord hypothermia. Moreover, active cooling with ambient temperature air flowing through underbody forced-air blankets may have potential to selectively cool torso (and spinal cord), similar to underbody torso-cooling pads.…”
mentioning
confidence: 99%